Bilateral cartilage T2 mapping 9 years after Mega-OATS implantation at the knee: a quantitative 3T MRI study. Issue 12 (December 2015) - Jungmann, P.M.; Brucker, P.U.; Baum, T.; Link, T.M.; Foerschner, F.; Minzlaff, P.; Banke, I.J.; Saier, T.; Imhoff, A.B.; Rummeny, E.J.; Bauer, J.S.
Summary: Objective: To evaluate morphological and quantitative MR findings 9 years after autograft transfer of the posterior femoral condyle (Mega-OATS) and to correlate these findings with clinical outcomes. Quantitative MR measurements were also obtained of the contralateral knee and the utility as reference standard was investigated. Design: Both knees of 20 patients with Mega-OATS osteochondral repair at the medial femoral condyle (MFC) were studied using 3T MRI 9 years after the procedure. MR-sequences included morphological sequences and a 2D multislice multiecho (MSME) spin echo (SE) sequence for quantitative cartilage T2 mapping. Cartilage segmentation was performed at the cartilage repair site and six additional knee compartments. Semi-quantitative MR observation of cartilage repair tissue (MOCART) scores and clinical Lysholm scores were obtained. Paired t -tests and Spearman correlations were used for statistical analysis. Results: Global T2-values were significantly higher at ipsilateral knees compared to contralateral knees (42.1 ± 3.0 ms vs 40.4 ± 2.6 ms, P = 0.018). T2-values of the Mega-OATS site correlated significantly with MOCART scores ( R = −0.64, P = 0.006). The correlations between MOCART and Lysholm scores and between absolute T2-values and Lysholm scores were not significant ( P > 0.05). However, higher T2 side-to-side differences at the femoral condyles correlated significantly with more severe clinical symptoms (medial, R = −0.53, P = 0.030; lateral, R = −0.51, P = 0.038). Conclusions: Despite long-term survival, 9 years after Mega-OATS procedures, T2-values of the grafts were increased compared to contralateral knees. Clinical scores correlated best with T2 side-to-side differences of the femoral condyles, indicating that intraindividual adjustment may be beneficial for outcome evaluation.